(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless sensor network (WSN) is employed to gather and forward information to the destination. It is very crucial to know the location of the event or collected information. This location information may be obtained using GPS or localization technique in wireless sensor networks. Randomly deployed WSN needs a large amount of GPS-enabled sensor nodes for localization, this necessitates progressive approach. However, nodes with sparse connectivity remain unlocalized. In this paper, a progressive mobile anchor based technique is proposed for node localization. Initially, sensor nodes are localized using anchors in the neighborhood, then these localized nodes progressively localized remaining nodes using multilateration. Mobile anchor node moves randomly in field and broadcast position information. It localized nodes with sparse connectivity. Simulation results show that proposed approach localize all sensor nodes with good accuracy